MiR‐124 Regulates Apoptosis and Autophagy Process in MPTP Model of Parkinson's Disease by Targeting to Bim. (11th June 2015) - Wang, Huiqing; Ye, Yongyi; Zhu, Zhiyuan; Mo, Liqian; Lin, Chunnan; Wang, Qifu; Wang, Haoyuan; Gong, Xin; He, Xiaozheng; Lu, Guohui; Lu, Fengfei; Zhang, Shizhong
Abstract: Parkinson's disease (PD) is the most prevalent movement disorder characterized by selective loss of midbrain dopaminergic (DA) neurons. MicroRNA‐124 (miR‐124) is abundantly expressed in the DA neurons and its expression level decreases in the 1‐methyl‐4‐pheny‐1, 2, 3, 6‐tetrahydropyridine (MPTP) model of PD. However, whether the upregulation of miR‐124 could attenuate neurodegeneration remains unknown. Here, we employed miR‐124 agomir and miR‐124 mimics to upregulate miR‐124 expression in MPTP‐treated mice and MPP + ‐intoxicated SH‐SY5Y cells, respectively. We found that loss of DA neurons and striatal dopamine in MPTP‐treated mice was significantly reduced by upregulating miR‐124. In addition, we identified a target of miR‐124, Bim that mediated the neuroprotection of miR‐124. Indeed, treatment of miR‐124 agomir in MPTP‐treated mice inhibited Bim expression, thus suppressing Bax translocation to mitochondria. Moreover, impaired autophagy process in MPTP‐treated mice and MPP + ‐intoxicated SH‐SY5Y cells characterized as autophagosomes (AP) accumulation and lysosomal depletion were alleviated by the upregulation of miR‐124. Taken together, these results indicate that upregulation of miR‐124 could regulate apoptosis and impaired autophagy process in the MPTP model of PD, thus reducing the loss of DA neurons.